Management of the Environmental Risk – an Economic-Social Priority - Constantin ANGHELACHE (Theoretical and Applied Economics, 2011)

(untitled)
The industrialization process, accelerated in the last decades of the 20th century and continued in the 21st century, determined, together with the beneficial effects manifested in the increase in quality of life, the appearance of some pollutants, especially in the areas where people live, work and entertain themselves. The risk is a situation/condition/event that, if occurs, generates an unfavorable effect both on the objectives, resources and reputation of the organization and on the successful achievement of its tasks/activities/mission. The environmental risk can manifest itself under the form of stressors (risk factors) generated by the human activity/inactivity and can generate adverse effects on the environment, and also the degradation and loss of sustainability. In order to ease the evaluation of the status/quality of the environment and facilitate the reporting and communication of the environmental performances of an organization, the present paper synthetically presents a series of environmental indicators, and also the description of the essential requirements of the voluntary environment standards in the ISO 14000 series.